PIWI proteins and piRNAs: key regulators of stem cell biology - Claro-Linares, Fernando; Rojas-Ríos, Patricia (Frontiers in Cell and Developmental Biology, 2025)
In this mini review, we discussed the functional roles of PIWI proteins and their associated small RNAs, piRNAs, in regulating gene expression within stem cell biology. Guided by piRNAs, these proteins transcriptionally and post-transcriptionally repress transposons using mechanisms such as the ping-pong amplification cycle and phasing to protect germline genomes. Initially identified in Drosophila melanogaster, the piRNA pathway regulate germline stem cell self-renewal and differentiation via cell-autonomous and non-cell-autonomous mechanisms. Precisely, in GSCs, PIWI proteins and piRNAs regulate gene expression by modulating chromatin states and directly influencing mRNA translation. For instance, the PIWI protein Aubergine loaded with piRNAs promotes and represses translation of certain mRNAs to balance self-renewal and differentiation. Thus, the piRNA pathway exhibits dual regulatory roles in mRNA stability and translation, highlighting its context-dependent functions. Moreover, PIWI proteins are essential in somatic stem cells to support the regenerative capacity of highly regenerative species, such as planarians. Similarly, in Drosophila intestinal stem cells, the PIWI protein Piwi regulates metabolic pathways and genome integrity, impacting longevity and gut homeostasis. In this case, piRNAs appear absent in the gut, suggesting piRNA-independent regulatory mechanisms. Together, PIWI proteins and piRNAs demonstrate evolutionary conservation in stem cell regulation, integrating TE silencing and gene expression regulation at chromatin and mRNA levels in somatic and germline lineages. Beyond their canonical roles, emerging evidence reveal their broader significance in maintaining stem cell properties and organismal health under physiological and pathological conditions.